LEGAL PROTECTION OF ADOPTED CHILDREN’S RIGHTS UNDER THE CIVIL CODE AND ISLAMIC INHERITANCE LAW - Adelia Rizki Wijayanti; Misranto Misranto; Sunardi Sunardi (SOSIOEDUKASI, 2026)
Child adoption transcends mere legal formality, representing a profound social and humanitarian responsibility. Its core must be the child’s best interests, not just fulfilling parental desires, thereby offering children a path to a more prosperous life. This research employs a normative juridical method, utilizing statutory and conceptual approaches to compare the legal protection of adopted children’s rights under the Civil Code and Islamic Inheritance Law. The findings reveal distinct paradigms. The Civil Code establishes adopted children in a position equal to biological children regarding custody, care, guardianship, and education. It ensures legal parity, administrative certainty, and prioritizes parental suitability for the child’s welfare. Conversely, Islamic law maintains the child’s lineage with their biological parents; adoption does not create a blood relationship. It is viewed as a social responsibility and virtuous deed. Nonetheless, Islam fundamentally supports initiatives for child protection and welfare. A key mechanism is the obligatory bequest (wasiat wajibah), which guarantees inheritance rights for adopted children. This provides concrete legal protection, as explicitly stipulated in Article 209 of the Compilation of Islamic Law (KHI), ensuring their financial security while honoring biological lineage principles. Thus, both systems, through different means, aim to safeguard the rights and future of adopted children.